Investigation of antioxidant activity from beetroot juice (Beta vulgaris L) as a healthy drink for the prevention of non-communicable disease - Ratih Tri Amelia; Tonang Dwi Ardyanto; Yulia Sari (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Non-communicable diseases can cause oxidative stress, which affects their pathophysiology. One of the recommended diets for preventing complications of non-communicable diseases (NCD) is a rich antioxidant diet. One of the foods rich in antioxidants is beetroots. This study aimed to assess the antioxidant content of locally obtained beetroot juice. Laboratory experimental methods were used to test the antioxidant activity of beetroot juice. Before the laboratory test, the panelists carried out a hedonic test. The beets were then juiced and checked for DPPH′ (2,2-diphenyl-1-picrylhydrazyl). The beetroot was then juiced and checked for DPPH′ (2,2-diphenyl-1-picrylhydrazyl). Statistical analysis was performed using the Kruskal–Wallis test. Results: The hedonic test showed that panelists preferred beetroot juice with lemon juice, with a 'like' range for the aroma and viscosity and a 'neutral-like' range for the taste and color of beetroot juice. The antioxidant content in 300 ml of beetroot juice was 53,34 ± 0,13%. In conclusion, beetroot juice has a high antioxidant content and health benefits in preventing NCD.